Role of Hormone on Tissue Health - Sudakshina Mukherjee1 , L.Malathi2 , N. Aravindha Babu3 , N.Anitha4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Endocrine system regulating hormonal function is one of the most important system of the body. Dysregulationin which can directly affect the oral cavity. Their systemic involvement also sometimes affects the oralhealth. Though other than diabetes mellitus and thyroid disorders rest of the hormonal diseases are rare butnot non-existent. So a proper knowledge about the clinical presentations should be kept by the dentists toavoid any risks and difficulties regarding their diagnosis. Conditions like burning mouth, dry oral cavity,and altered tastes can also be an after effect of menopause should be ruled out by dentist before coming to adefinitive diagnosis. Careful counseling of the patients especially women regarding their conditions shouldbe done by keeping in mind the psychological stress they undergo during that stage of life. So this reviewcirculates around the oral manifestations due to hormonal imbalance in a human body and post menopausalwomen.